Konsep Al-Ashr dalam Pendidikan Islam - Siregar, Nur Azizah; Suryani, Ira; Pasaribu, Safrina Putri; Bunaiyya, Dila (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This journal aims to uncover the meaning of Surah Al-Ashr (103): 1-3, which can then serve as an indication for the concept of Islamic knowledge. The Prophet, as a role model for all Muslims, is also the best teacher in applying the meaning of Surah Al-Ashr. This surah describes the characteristics of people who waste their time on unproductive matters, which is relevant to how the Prophet spent his time teaching Islamic Education to his community.